Strategi Komunikasi Organisasi Pengurus Dalam Merekrut Kader Penggerak Nahdlatul Ulama Di Kabupaten Padang Lawas - Siti Permata Daulay; Ali Sati; Juni Wati Sri Rizki (Hikmah, 2025)
An organization must have the ability to implement its work programs effectively. To execute an organization's work programs, a significant number of people are needed. Therefore, the Nahdlatul Ulama Branch Leadership (PCNU) of Padang Lawas conducts member recruitment through kader penggerak (mobilizing cadres). Member recruitment is essential to ensure the continuity of an organization so that it remains active and operational. The recruitment strategy is a series of fundamental decisions and actions made by the organization's management to help formulate policies and organizational goals. The theories used in this thesis include the constructivist paradigm, organizational culture theory, and persuasive communication theory. The objective of this study is to identify the strategies used in the participant recruitment process. This research employs the ethnomethodology approach, which is a set of methods within qualitative research that focuses on the interpretation of practical reality. Ethnomethodological research is classified as qualitative research because it produces descriptive data obtained through the observation of speech, writing, and the behavior of the research subjects. Within the framework of qualitative research, ethnomethodology serves as a theoretical foundation for a research method. Based on the research conducted by the author, the Nahdlatul Ulama of Padang Lawas Regency has implemented three strategies in recruiting kader penggerak participants. The first strategy is through engaging messages, the second is through social media outreach on platforms such as Facebook, and the third is utilizing mass media by broadcasting on Namora FM 99.5 radio and inviting influential figures.